2022
DOI: 10.1088/1748-9326/ac7601
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and health in Kuwait: temperature and mortality projections under different climatic scenarios

Abstract: Background–It is uncertain what climate change could bring to populations and countries in the hot desert environment of the Arabian Peninsula. Not only because they are already hot, countries in this region also have unique demographic profiles, with migrant populations potentially more vulnerable and constituting a large share of the population. In Kuwait, two-thirds of the population are migrant workers and record-high temperatures are already common. Objective–We quantified the temperature-related mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…One possible explanation could be an increased exposure to outdoor air pollution among adults, potentially resulting from outdoor work activities; however, we acknowledge that this is speculative and further research is needed to confirm this hypothesis. Second, the existing literature in Kuwait shows a clear health disparity between Kuwaitis and the non-Kuwaiti migrant workers [31][32][33][34][35]. For example, examining the effects of dust storm compared to non-dust storm days on mortality showed an effect measure modification by nationality in Kuwait where non-Kuwaitis were more vulnerable [15].…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation could be an increased exposure to outdoor air pollution among adults, potentially resulting from outdoor work activities; however, we acknowledge that this is speculative and further research is needed to confirm this hypothesis. Second, the existing literature in Kuwait shows a clear health disparity between Kuwaitis and the non-Kuwaiti migrant workers [31][32][33][34][35]. For example, examining the effects of dust storm compared to non-dust storm days on mortality showed an effect measure modification by nationality in Kuwait where non-Kuwaitis were more vulnerable [15].…”
Section: Discussionmentioning
confidence: 99%
“…Heat stress itself is responsible for major negative impacts on human health (e.g., Alahmad et al, 2022;Chapman et al, 2022;Fan et al, 2022;Kovats & Hajat, 2008;Zander et al, 2015). There are several examples of catastrophic heat stress events that occurred in the past, such as the one that hit Chicago in 1995, resulting in more than 700 fatalities (Dematte et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study indicated that there has been an increase in temperature of up to 1.9 °C during the last 50 years [ 33 ]. Being the hottest region in the world and fulfilling its water demands by non-conventional means (mostly desalination), adverse impacts of climate change are still expected despite GCC's resilience to extreme conditions and environmental security if the global society fails to curb global temperature rise [ [33] , [34] , [35] , [36] ]. Thus, water and climate scenarios may challenge the GCC countries to achieve SDGs 6 and 13.…”
Section: Introductionmentioning
confidence: 99%